Interactive deformable music generation system - Tay, Jaslyn (Nanyang Technological University, 2021)
This project seeks to develop an exploratory music experience using a deformable surface for music generation. An Android device captures the input on the surface and the input is processed using the Open CV library’s Color Blob Detection [8]. A set of classes (Synthesizer.java, AudioGenerator.java) by Periklis Ntanasis [10][11] is further developed and incorporated to create the sounds. A prototype of the project was put through a usability test to evaluate its effectiveness in attaining its goal of music exploration. Users were asked to carry out basic orientation tasks and to create pieces of music with the system.